2015
DOI: 10.4314/ijbcs.v8i5.3
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides use in cocoa sector in Cameroon: characterization of supply source, nature of actives ingredients, fashion and reasons for their utilization

Abstract: The chemical control is the widely control method applied in Cameroon for pests and diseases by all the cocoa producers without technical suitable assistance by the State as before 1980'S. However, it is known that farmers have less knowledge on the good pesticides use for the control of a specific pest. The objective of this study was to provide insight in current pesticide use in the cocoa sector in Cameroon. A stratified sampling scheme was used. A total of 251 cocoa farmers, 20 post-harvest cocoa traders a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 11 publications
3
51
0
1
Order By: Relevance
“…In Cameroon, pesticides are largely used by farmers and traders to protect their growing plants and products in the field and during storage [3,4,5,6,7]. Despite the numerous advantages of pesticide use in agriculture, there is a need for scientific evaluation and control of these products.…”
Section: Introductionmentioning
confidence: 99%
“…In Cameroon, pesticides are largely used by farmers and traders to protect their growing plants and products in the field and during storage [3,4,5,6,7]. Despite the numerous advantages of pesticide use in agriculture, there is a need for scientific evaluation and control of these products.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, potential cocoa yield losses as a result of black pod disease could be between 20-30% (Ndoumbe-Nkeng et al, 2004; Drenth and Guest, 2004). Another estimate indicated that potential global cocoa production losses as a result of black pod and pod rot fungal diseases could be as high as 44% (Mahob et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…(Mahob et al, 2014) is a notorious form of attack on cocoa pods, which often accounts for significant yield losses depending on the effectiveness of adopted management practices and timeliness of spraying cocoa pods with appropriate agrochemicals (Guest, 2007). Specifically, potential cocoa yield losses as a result of black pod disease could be between 20-30% (Ndoumbe-Nkeng et al, 2004; Drenth and Guest, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Production and revenues from cocoa could be substantially higher if the plants were not confronted with strong parasitic pressures, diseases and insect pests (Mahob et al, 2014). Inorder to achieve this desire, farmers are engaged in the use of pesticides that reduces parasitic pressures to acceptable levels (Tadu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%